Emerging Skill in Multi-Year Prediction of the Indian Ocean Dipole - Feba, F.; Ashok, Karumuri; Collins, Matthew; Shetye, Satish R. (Frontiers in Climate, 2021)
The Indian Ocean Dipole is a leading phenomenon of climate variability in the tropics, which affects the global climate. However, the best lead prediction skill for the Indian Ocean Dipole, until recently, has been limited to ~six months before the occurrence of the event. Here we show that multi-year prediction has made considerable advancement such that, for the first time, two general circulation models have significant prediction skills for the Indian Ocean Dipole for at least two years after initialization. This skill is present despite ENSO having a lead prediction skill of only one year. Our analysis of observed/reanalyzed ocean datasets shows that the source of this multi-year predictability lies in sub-surface signals that propagate from the Southern Ocean into the Indian Ocean. Prediction skill for a prominent climate driver like the Indian Ocean Dipole has wide-ranging benefits for climate science and society.